Metformin-Associated Acute Kidney Injury and Lactic Acidosis - David Arroyo; Rosa Melero; Nayara Panizo; Marian Goicoechea; Patrocinio Rodríguez-Benítez; Soledad García Vinuesa; Eduardo Verde; Alberto Tejedor; José Luño (International Journal of Nephrology)
Objectives. Metformin is the preferred oral antidiabetic agent for type 2 diabetes. Lactic acidosis is described as a rare complication, usually during an acute kidney injury (AKI). Material and Methods. We conducted a prospective observational study of metformin-associated AKI cases during four years. 29 cases were identified. Previous renal function, clinical data, and outcomes were recorded. Results. An episode of acute gastroenteritis precipitated the event in 26 cases. Three developed a septic shock. Three patients died, the only related factor being liver dysfunction. More severe metabolic acidosis hyperkalemia and anemia were associated with higher probabilities of RRT requirement. We could not find any relationship between previous renal dysfunction and the outcome of the AKI. Conclusions. AKI associated to an episode of volume depletion due to gastrointestinal losses is a serious complication in type 2 diabetic patients on metformin. Previous renal dysfunction (mild-to-moderate CKD) has no influence on the severity or outcome.